Heterologous prime-pull mucosal vaccination with an adjuvanted RBD vaccine elicits robust IgA production and protects against SARS-CoV-2 - Hirsch, Allyson H.; Ellsworth, Calder R.; Lewis, William A.; Craig, Ryan; Meyer, Amy E.; Maldonado, Jonatan; Ramirez Lopez, Frania; Thimmiraju, Syamala Rani; McLachlan, James B.; Qin, Xuebin; Maness, Nicholas J.; Pollet, Jeroen; et al. (Frontiers in Immunology, 2025)
Despite the efficacy of approved severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccines in preventing severe disease and death, breakthrough infections continue to occur in vaccinated individuals, contributing to further viral mutation and spread. These limitations may be attributable to the poor induction of mucosal immunity by parenteral vaccination. Mucosal adjuvants, such as T-vant, can enhance vaccine-induced immune responses through the generation of antigen-specific antibodies and T cells in the respiratory tract. In this study, we evaluated the protective efficacy of adjuvanted SARS-CoV-2 receptor binding domain (RBD) subunit vaccines administered by homologous and heterologous routes. Immunized mice were challenged with SARS-CoV-2-XBB.1.5 and monitored for weight loss and survival. Lung and nasopharynx tissues were collected at pre-scheduled timepoints to assess viral loads and histopathology. Additionally, vaccine-induced humoral and cell-mediated immune responses were evaluated in the mucosal and systemic compartments. A prime-pull vaccination strategy – comprising an intramuscular prime immunization with aluminum hydroxide (alum) and CpG-adjuvanted RBD followed by an intranasal boost with T-vant-adjuvanted RBD – conferred protection against mortality and lung pathology and cleared virus from the nasopharynx by three days post infection. The prime-pull vaccine regimen elicited superior anti-RBD IgA in the bronchoalveolar lavage fluid and nasal washes, when compared to other vaccine groups. Given that much of the global population has already received parenteral SARS-CoV-2 vaccination or has been naturally exposed, a prime-pull approach could leverage pre-existing systemic immunity using a single mucosal boost.